2003
DOI: 10.1128/iai.71.3.1316-1320.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Glutathione Is Required for Pertussis Toxin Secretion by Bordetella pertussis

Abstract: The abilities of cysteine-containing compounds to support growth of Bordetella pertussis and influence pertussis toxin transcription, assembly, and secretion were examined. Cysteine is an essential amino acid for B. pertussis and must be present for protein synthesis and bacterial growth. However, cysteine can be metabolized to sulfate, and high concentrations of sulfate can selectively inhibit transcription of the virulence factors, including pertussis toxin, via the BvgAS two-component regulatory system in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Since B. pertussis is an obligate aerobe, testing for direct oxygen oxidation is tech- nically not feasible. Cystine is a required growth factor for B. pertussis; thus, completely removing it from growth media is not possible (53,54). However, changing the levels of cystine did not perturb cytochrome c synthesis (not shown).…”
Section: And 5 [Example Of Results With Cb75])mentioning
confidence: 99%
“…Since B. pertussis is an obligate aerobe, testing for direct oxygen oxidation is tech- nically not feasible. Cystine is a required growth factor for B. pertussis; thus, completely removing it from growth media is not possible (53,54). However, changing the levels of cystine did not perturb cytochrome c synthesis (not shown).…”
Section: And 5 [Example Of Results With Cb75])mentioning
confidence: 99%
“…The holotoxin contains 11 disulfide bonds: one in S1, two in S4 and S5, and three in S2 and S3. The periplasmic disulfide bond‐catalyzing proteins DsbA‐C and reduced glutathione disulfides are required for efficient PTX assembly [18,19]. Holotoxin assembly takes place in the periplasm even in the absence of the Ptl machinery, as shown by studies conducted both in vivo and in vitro [20–23].…”
Section: Biogenesis Of Ptxmentioning
confidence: 99%
“…2). It was reported that there is no difference in Prn production by Tohama I cultured in modified SS medium compared to that in a culture in modified SS medium containing DTT, a reducing agent (27). These results suggest that BvgAS-regulated virulence factors other than type III secreted proteins are not affected by reducing agents.…”
Section: Discussionmentioning
confidence: 73%